Capacitatea de răspuns a politicilor sociale de ocupare la nevoile de angajare în muncă a persoanelor cu handicap - Drăghici, Elisaveta (Calitatea Vieții, 2009)
The research conducted in the Municipality of Braila, between January and March 2008 aimed to underline the consequences (effects) of the employment policies on the lives of handicapped persons. The measures of stimulating the employment of handicapped persons were recently diversified, now including both passive and active measures. The extent of the knowledge of these measures by the population is influencing the level of their unfolding (development). We aimed to reveal the level of their knowledge by the population and the capacity of these policies to satisfy the needs/requests of the handicapped people.